2019
DOI: 10.1111/ijfs.14127
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes in almonds throughout storage: modeling the effects of common industry practices

Abstract: Summary Further investigations of almond degradation under typical industrial storage conditions from a quantitative perspective are warranted. This study modeled effects of packaging, temperature (TEMP), relative humidity (RH) and roasting on chemical attributes of almonds stored according to common industry practices throughout 16 months. Roasted samples were stored in high‐barrier bags (HBB) or polypropylene bags (PPB) at multiple combinations of TEMP and RH. Raw samples were held in unlined cardboard carto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A recent study measured the FFA levels of PO pasteurized raw almonds under similar storage conditions (35 °C/65% RH) and reported similar FFA levels at 0.11 per storage month rate. 36 The rate of FFA increase over 12 months of storage was also highest in controls relative to the PO > MH treatments. Increased levels of FFAs correspond to rancid development, unpleasant sensory attributes (e.g., soapy), and flavor development in cheese.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A recent study measured the FFA levels of PO pasteurized raw almonds under similar storage conditions (35 °C/65% RH) and reported similar FFA levels at 0.11 per storage month rate. 36 The rate of FFA increase over 12 months of storage was also highest in controls relative to the PO > MH treatments. Increased levels of FFAs correspond to rancid development, unpleasant sensory attributes (e.g., soapy), and flavor development in cheese.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, the PV in 80% RH exceeded the maximum limit of food rancidity (10 meq Kg −1 ) in the 240 days of storage. Almonds stored at 50% RH showed more stable storage stability than 60% (Parrish et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The higher the RH in the external environment was, the more significant the rising trend was. By measuring chemical changes in almonds throughout the storage period, the researchers found that samples stored at 50% RH exhibited greater stability than those stored at 65% RH (Parrish et al ., 2019). Arachidonic acid, a small amount of SFA in peanuts, was significantly reduced during storage ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is of great interest in the extraction of oils from plants and exploring their antioxidant activities. Almonds ( Prunus amygdalus L.) are one of the most popular nuts, widely grows in temperate zones in most countries of the world and are often used as an ingredient in processed foods (Sang et al ., 2002; Matthäus et al ., 2018; Parrish et al ., 2019). In addition, almonds are rich in unsaturated fatty acids and bioactive substances, making them beneficial to human health, including anti‐cancer, anti‐tumour and antioxidant properties (Shi et al ., 2019; Banjanin et al ., 2020; Özcan et al ., 2020, 2021).…”
Section: Introductionmentioning
confidence: 99%